“Maria, Maria, Marias”: a trajetória de profissionalização das egressas do curso de Pedagogia do PROFEBPAR do município de Grajaú-MA - SILVA, Patricia Alves (2021)
The present research is part of the research line: Educational Institutions, Curriculum, Training and Teaching Work of the PPGE/UFMA. Entitled as “MARIA, MARIA, MARIAS”: The trajectory of professionalization of the graduates of the Pedagogy course at PROFEBPAR in the municipality of Grajaú - MA. It aimed to analyze the trajectory of professionalization of the graduates of the Pedagogy course from the aforementioned program. In this study, I adopted the qualitative research methodology in a critical perspective, to give voice and visibility to student teachers in order to highlight the elements that constituted the graduates' professionality. This study articulates the bibliographical research based on Nóvoa (1992), Sacristán (1999), Pimenta (1997), Libâneo (2015), Vicentini and Lugli (2009), Oliveira (2010), Tardif (2013), Brzezinski (2016 ), Gatti et al (2019) among others that allowed me to understand the professionalization of teachers in Brazil and the educational contexts of the teaching profession. The documental research involved training documents such as enrollment and monitoring of graduates during the course, as well as the Pedagogical Project of the PROFEBPAR Pedagogy course. In order to give voice and visibility to the trajectory of the graduates, I used Schutze's narrative interview (2011), as well as an analysis of the narratives proposed by him. The results of the analysis of the graduates' professionalization trajectory revealed that the definition of being a teacher took place before the conscious choice of the profession, being associated with childhood memories, games and school experiences. The undergraduate course contributed to the construction of professionalism, through the acquisition of skills, habits and skills developed in school and professional life. In summary, the PROFEBPAR Pedagogy course developed a feeling of belonging and engagement with the teaching profession.